Analisis Reaksi Pasar Saham di Sektor LQ45 Sebelum dan Sesudah Peristiwa Peringatan Darurat Garuda Biru: Studi Average Abnormal Return dan Trading volume activity - Annisa Abdullah; Wendy (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The Blue Garuda Emergency Alert event was first announced on August 21, 2024, through the Instagram account of Narasi by Najwa Shihab. This study aims to analyze the stock market reaction before and after the event, focusing on companies included in the LQ45 stock index on the Indonesia Stock Exchange. Hypothesis testing was conducted using a paired sample t-test for Average Abnormal Return (AAR) with SPSS, while Trading Volume Activity (TVA) was tested using the Wilcoxon Signed-Rank Test due to the non-normal distribution of the data. This event study observes a 10-day window before and after the Blue Garuda Emergency Alert event. The expected return was calculated using the market model with an estimation period of 200 trading days. The results of the study indicate a significant difference in Average Abnormal Return (AAR) before and after the event, with a significance value of 0.027. Additionally, Trading Volume Activity (TVA) also showed a highly significant change, with a significance value of 0.000. These findings suggest that the Blue Garuda Emergency Alert had a tangible impact on the stock market, both in terms of abnormal returns and trading volume activity, reflecting the market's reaction to the event.